Tracked Changes. Microbiology of the food chain. Horizontal method for the enumeration of coagulase-positive staphylococci (Staphylococcus aureus and other species). Method using rabbit plasma fibrinogen agar medium Part 2, (21st October 2021) - British Standards Institution,
No abstract available